Дослідження процесу розгону машинно-тракторного агрегату з гідрокерованою трансмісією у процесі виконання транспортної роботи - Кальченко, Борис Іванович; Кожушко, Андрій Павлович; Пелипенко, Євген Сергійович; Ярита, Олександр Олександрович (Харківський національний автомобільно-дорожній університет, 2019)
Наведено математичну модель процесу розгону машинно-тракторного агрегату під час виконання транспортної роботи, за допомогою якої можна оцінювати критерії розгінних якостей транспортного засобу з трансмісією, у якій перемикання передач здійснюється під навантаженням завдяки гідрокерованим фрикційним муфтам.

Nowadays, in the process of selecting modern agricultural machinery, there is a problem to choose the necessary power-unit. An overview of different types of transmissions used in the designing of a modern wheeled tractor is presented. Stepped mechanical transmissions (with gear shifting by moving gears, stepped synchronized, with gear shifting under pressure of hydraulic friction clutches) and stepless mechanical transmissions (hydromechanical, hydraulic-mechanical, electromechanical and a transmission device comprising a variator) are presented. The advantages and disadvantages of using certain types of transmissions are emphasized. It has been established that the most rational type of transmission is mechanical with gear shifting with the help of hydraulic friction clutches. It is caused by the convenience of an operator-driver’s work and construction safety demands are met. The goal of the work is tuning of the mathematical apparatus to determining the dynamic load in a transmission, in which gear shifting is carried out by the hydraulic friction clutches, due to study of the transition process of achieving working speed of the machinetractor unit during performing the transport work. In solving the set goal, a methodology that provided the creation of a mathematical apparatus based on theoretical study of a multivariate dynamic system was used. The developed mathematical model considers the external perturbation of the road surface, and also the exponential form of change is used in modeling of control systems with the help of hydraulic friction clutches As a result, a mathematical model of the acceleration process of a wheeled machine-tractor unit during transport work is obtained, with the help of which it is possible to evaluate the criteria of acceleration qualities of a vehicle with a transmission, in which gear shifting is carried out under load due to the hydraulic friction clutch. The originality novelty is to obtain further development of the mathematical model of a machine-tractor unit with a transmission, in which gear shifting takes place with the help of hydraulic friction clutches in the process of achieving the working speed. The practical value of the work is in the recommendations on the use of one or another combination of engaging of friction clutches. The given recommendations are based on the analysis of acceleration characteristics, namely the work of hitching and the dynamic load index on the input elements of the gearbox.
Research of acceleration machine-tractor unit with hydrocontrolled transmission when performing transport work
Keywords: колісний трактор; транспортна робота; фрикційна муфта; математична модель; розгін; wheeled tractor; transport operation; friction clutch; mathematical model; acceleration